Pupils' view of mathematics : initial report for an international comparison project - Pehkonen, Erkki (Research report / Department of Teacher Education, University of Helsinki, 1995)
Tiivistelmä: Oppilaiden matematiikkakuva : kansainvälisen vertailuprojektin alkuraportti.
Keywords: oppiminen; matematiikka; kansainvälinen vertailu; oppilaat; käsitykset; opetus; koululaiset